Sistem Informasi Pengelolaan Stok dan Distribusi LPG 3Kg di PT Gasindo dengan Safety Stock & Reorder Point - Nugroho, Adi; Setiaji, Pratomo; Nugraha, Fajar; Setiawan, Arif (Sekolah Tinggi Teknologi Dumai, 2025)
Stock management at PT. Gasindo Raya Utama is a system designed to simplify stock management and facilitate accurate decision-making processes. The purpose of this system is to design an information system that supports the management of 3 kg LPG stocks at PT. Gasindo Raya Utama by implementing the Safety Stock and Reorder Point methods. This system is intended to help the company prevent stock shortages and determine the timing and quantity of reorder effectively. The Safety Stock method is applied to calculate the minimum reserve stock required to anticipate fluctuations in demand or supply delays. Meanwhile, the Reorder Point method is used to determine the reorder point based on daily consumption levels and lead times. The implementation of this system is expected to improve the efficiency of stock management, minimize the risk of stockouts, and ensure that LPG distribution runs smoothly in accordance with the needs of the community.